Vidio Profil Fakultas Sains Dan Teknologi Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi - Danial, Ahmad; Khotib Zubiyan, Ahmad; Sepriano, Sepriano (Jurnal Syntax Fusion, 2023)
Multimedia is one of the right tools to convey information in the form of audio and video. Multimedia is also capable of producing something that can be interesting. Faculty of Science and Technology, Islamic University of Sulthan Thaha Saifuddin Jambi doesn’t have a video profile for information purposes yet. Social media can be a tool for promoting a product/service/company to be better known by the wider community. The oldest promotional media is word of mouth. This media is indeed very effective, because the speed of delivery cannot be measured and estimated. Along with the development of the times, promotional media are also becoming more interesting and more innovative, including promotional media in the form of video profiles. Through this profile video, it is hoped that the public cand find general information about the Faculty of Science and Technology, Islamic University of Sulthan Thaha Saifuddin Jambi.